ANALISIS YURIDIS TAFSIR KONSTITUSIONALITAS TERHADAP FRASE ORGANISASI ADVOKAT DALAM UNDANG-UNDANG NOMOR 18 TAHUN 2003 - Sofyan Joesoef; Idham Chalid; Jalaludin (TADULAKO MASTER LAW JOURNAL, 2024)
The purpose of this research is to find out the Constitutional Court's decision on the constitutionality interpretation of the phrase "Advocate Organization" in Law Number 18 of 2003 concerning Advocates which is authoritative in nature as a juridical basis, and the method used is to carry out research which is of a Normative Juridical nature using legal, case (decision), historical and conceptual approaches. Types of legal materials come from primary and secondary legal materials, which are collected by means of literature searches/studies. The analysis technique uses a descriptive analytical method which in the process of drawing conclusions is carried out using deductive logic. The results of this research provide the conclusion that constitutionally the definition given is that the only forum for the Advocate profession as intended in the Law on Advocates is the only forum for the Advocate profession which has the authority to carry out special education for the Advocate profession [Article 2 paragraph (1)], examination of prospective Advocates [Article 3 paragraph (1) letter f], appointment of Advocates [Article 2 paragraph (2)], creating a code of ethics [Article 26 paragraph (1)], forming an Honorary Council [Article 27 paragraph (1)], forming The Supervisory Commission [Article 13 paragraph (1)], carries out supervision [Article 12 paragraph (1)], and dismisses advocates [Article 9 paragraph (1), Law on Advocates]. The constitutional interpretation given by the Constitutional Court is authoritative and must be used as a juridical basis which is coercive and binding.